LOYALITAS PELANGGAN BROWNIES AMANDA BERDASARKAN HARGA, KUALITAS PELAYANAN DAN MEREK - TUKINAH, UKIE; Arma, Aulia (JURNAL STIE SEMARANG, 2025)
The culinary business is a business that is growing rapidly even during times of crisis. This is based on the fact that food is one of the basic human needs that must be fulfilled and prioritized. The diverse food business or culinary business makes people curious to try whatever types are trending in society. One of them is Brownies Amanda, a food company that already has many branches outside the region. Amanda's Brownies have become an iconic souvenir that is popular with immigrants visiting the area. The purpose of this research is to determine the influence of price, service quality and brand on customer loyalty at Brownies Amanda Branch in Boyolali.The method in this research is a quantitative method, with data collection carried out using interviews, case studies and questionnaires where the number of samples used was 81 respondents. The analytical methods used are validity test, reliability test, classist assumption test, correlation test, multiple linear regression analysis, T test and coefficient of determination test.Based on the research results, it can be concluded: 1) Price has a positive and significant effect on Customer Loyalty at Brownies Amanda Branch in Boyolali seen from the significance value of 0.002<0.05. 2) Service Quality has a positive and significant effect on Customer Loyalty at Brownies Amanda Branch in Boyolali seen from the significance of 0.000<0.05. 3) The brand has a positive and significant effect on Customer Loyalty at Brownies Amanda Branch in Boyolali, seen on the day the significance value is 0.028<0.05.So it can be concluded that price, service quality and brand have a positive and significant effect on customer loyalty at Brownies Amanda Branch in Boyolali. It is recommended to Brownies Amanda to maintain and improve product quality according to the price quoted, to provide a suggestion box equipped with pen and paper so that consumers can express their aspirations along with criticism and suggestions, to offer member cards or other offers to attract consumers' interest in doing so. repeat purchase. It is recommended that future researchers pay attention to other variables besides the variables discussed in this research that influence the customer loyalty variable so that they can become references for future researchers and can extend the research time.